Supercritical CO2 impregnation process applied to polymer samples preparation for dynamic nuclear polarization solid‐state NMR. (7th September 2022) - Le, Dao; Frison, Amélie; Masmoudi, Yasmine; Bouledjouidja, Abir; Thureau, Pierre; Mollica, Giulia; Badens, Elisabeth; Ziarelli, Fabio; Viel, Stéphane
Abstract: In this study, supercritical CO2 (scCO2 ) was used to impregnate polymers with paramagnetic polarizing agents to prepare samples for dynamic nuclear polarization (DNP) solid‐state NMR (ssNMR) experiments. As a proof of concept, we impregnated polystyrene samples with bTbK, which stands for bis‐TEMPO‐bisketal where TEMPO is 2, 2, 6, 6‐tetra‐methylpiperindin‐1‐oxyl. Substantial DNP signal enhancements could be measured on DNP‐enhanced 1 H → 13 C cross‐polarization (CP) magic‐angle spinning (MAS) spectra recorded at 9.4 T and 100 K, reaching a maximum value of 8 in the most favorable case, which appeared comparable or even higher than what is typically obtained on similar systems for former sample preparation methods. These results highlight the potential of scCO2 impregnation as an efficient and possibly versatile methodology to prepare polymer samples for DNP ssNMR investigations. Abstract : Supercritical CO2 impregnation is a promising method to impregnate polymers with biradicals to perform low‐temperature dynamic nuclear polarization magic‐angle spinning NMR experiments with enhanced sensitivity.